Does fracture obliquity in Weber B fibula fractures correlate with mortise instability?. Issue 11 (November 2019) - Velasco, Brian T.; Miller, Christopher P.; Ye, Michael Y.; Kwon, John Y.
Highlights: Significant variations in Weber B fibula fracture length, height, and obliquity are seen clinically. Increased fracture length, height and obliquity do not correlate with a higher incidence of mortise instability. Future studies should identify radiographic parameters of distal fibula fractures that are most predictive of instability. Abstract: Background: The diagnosis of instability in the apparent, isolated distal fibula fracture can be challenging and often necessitates stress radiography. Danis & Weber classified lateral malleolar fractures based on the level of the fracture in relation to the syndesmosis. While Weber B fractures occur at the level of the syndesmosis, some such injuries present with a long, oblique pattern extending well above the syndesmosis. Given the well-established literature demonstrating that fractures above the syndesmosis correlate with a higher level of concomitant syndesmotic and deltoid ligament injury, we hypothesize that increased fracture obliquity, length and height of Weber B fibula fractures similarly correlates with increased mortise instability. Methods: All patients with isolated Weber B fibula fractures who underwent gravity stress radiography met inclusion criteria. Fracture height was measured on mortise radiographs as: (1) the distance from the distal tip of the fibula to fracture apex, (2) the distance to the fracture apex as measured on a line drawn perpendicular to a line parallel to the plafond, (3) an angle subtended by a line drawn parallel to the plafond and a line drawn to the fracture apex and (4) a ratio of the absolute length as compared to fibular width. Results: 51 patients were included in the study. The group of 39 patients with stable ankles had a mean medial clear space of 3.12 ± 0.65 mm (range, 1.5 mm to 4.0 mm). The group of 12 patients with unstable ankles had a mean medial clear space of 6.29 ± 3.11 mm (range, 4.1 mm to 14.0 mm). These groups showed no significant difference in fracture angle (p = 0.93), fracture height from plafond (p = 0.49), fracture height from tip of fibula (p = 0.42), and as a ratio of absolute length to fibular width (p = 0.85). Conclusion: Increased fracture obliquity, length and height of Weber B fibula fractures did not correlate with a higher incidence of mortise instability. Despite the lack of positive correlation, future studies should continue to investigate and identify radiographic parameters of distal fibula fractures that are most predictive of instability.